Diagnosis and management of inhalation injury: an updated review. Issue 1 (December 2015) - Walker, Patrick; Buehner, Michelle; Wood, Leslie; Boyer, Nathan; Driscoll, Ian; Lundy, Jonathan; Cancio, Leopoldo; Chung, Kevin
Abstract In this article we review recent advances made in the pathophysiology, diagnosis, and treatment of inhalation injury. Historically, the diagnosis of inhalation injury has relied on nonspecific clinical exam findings and bronchoscopic evidence. The development of a grading system and the use of modalities such as chest computed tomography may allow for a more nuanced evaluation of inhalation injury and enhanced ability to prognosticate. Supportive respiratory care remains essential in managing inhalation injury. Adjuncts still lacking definitive evidence of efficacy include bronchodilators, mucolytic agents, inhaled anticoagulants, nonconventional ventilator modes, prone positioning, and extracorporeal membrane oxygenation. Recent research focusing on molecular mechanisms involved in inhalation injury has increased the number of potential therapies.